Pemanfaatan TikTok sebagai Media Dakwah antara Kreativitas dan Etika Komunikasi Islam - Siti Maudillah; Adiba Syaidatun Nisa; Adhi Kusuma (Lembaga Pengembangan Kinerja Dosen, 2025)
This research discusses the use of TikTok as a medium for da'wah among the younger generation, which is an integral part of the development of da'wah communication in the digital era. With its engaging short video format, TikTok offers preachers the opportunity to reach a wider audience. However, there are challenges related to communication ethics and the substance of da'wah that need to be overcome to maintain the relevance and accuracy of the message. The aim of this research is to analyze how the creativity of da'wah content can be integrated with the ethical principles of Islamic communication, as well as identifying the impacts and challenges faced. Findings show that 70 percent of respondents use TikTok for more than an hour every day, and 65 percent believe this platform is effective as a medium for preaching. However, challenges such as the spread of invalid information and the commercialization of da'wah still exist. This research recommends the need for interactive communication strategies and collaboration with experts to ensure the accuracy and integrity of da'wah content. With a wise approach, the use of TikTok can be an effective tool for spreading peaceful and inclusive Islamic values.